An overlooked influence of reactive oxygen species on ammonia-oxidizing microbial communities in redox-fluctuating aquifers. (15th April 2023) - Wang, Helin; Li, Ping; Liu, Xiaohan; Zhang, Jing; Stein, Lisa Y.; Gu, Ji-Dong
Highlights: Dynamic AOM successions were found covariant with in-field or in-lab ROS gradient. Oxidation resistances differed significantly among three AOM isolates exposed to ROS. ROS might act as another key factor affecting AOM in redox-fluctuating environments. ROS decreased the amoA gene expression of AOA strain Nitrososphaera viennensis PLX03. Abstract: Reactive oxygen species (ROS) are ubiquitous in O2 -perturbed aquifers, but their role in shaping ammonia-oxidizing microbial communities is not clear. This study examined the dynamic responses of ammonia-oxidizing microorganisms (AOMs) in redox-fluctuating aquifers to ROS via field investigation and in-lab verification using transcriptomes/ metatranscriptome and RT-qPCR. Ammonia-oxidizing archaea (AOA) dominated recharge aquifers with lower ROS levels, whereas ammonia-oxidizing bacteria (AOB) and heterotrophic nitrifying aerobic bacteria (HNB) predominated in discharge areas with higher ROS levels. Similar succession in AOM enrichments was found in that the dominant AOMs changed from AOA Nitrosopumilus to AOB Nitrosomonas with increasing ROS. Ammonia oxidation and antioxidant capacity differed significantly among three AOM isolates exposed to ROS. ROS decreased the amoA gene expression of AOA strain Nitrososphaera viennensis PLX03, accompanied by inhibited ammonia oxidation capacity. By contrast, the catalase and superoxide dismutase activities of the AOB strain Nitrosomonas oligotropha PLL12 and HNB strain Pseudomonas aeruginosa PLL01 increased, and the antioxidant genes katG, sodA, ahpC, and ahpF were significantly upregulated. These results demonstrate that ROS exert an important influence on AOMs in redox-fluctuating aquifers. This study improves our understanding of the ecological niches of AOMs in surface/subsurface environments. Graphical Abstract: Image, graphical abstract